Penerapan Metode Regresi Linier Berganda Terhadap Pengaruh Jumlah Karyawan dan Jumlah Alat/Mesin PT. Binivan Konstruksi Abadi Tahun 2014-2018 - Grace Johanna Simanjuntak grace; T.J. Marpaung marpaung; Y.B. Siringoringo siringoringo (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Stone is a building material that is commonly used as a foundation construction, because the nature of the stone is not easily changed shape and maintained quality even though embedded in the ground. The production of this stone is only influenced by the number of employees (), the number of tools or machines available (). These factors cause higher production. In the data research used is data in 2014-2018, the method used is multiple linear regression, This analysis is used to determine the direction of the relationship between variables bound to free variables, large coefesien korelaso and coeffesien determination and find out whether each variable is related positively or negatively using secondary data types. The results of this study obtained that F_hitung? F_tabel and concluded that was rejected stating that there was a significant relationship between the two free variables and bound variables, The correlation value is 0.99973 and the result of the determination coefficient is 0.98327, which means that 98.327% of split stone production results are influenced by the number of employees and the number of tools /machines, and the rest is influenced by other factors.